Peningkatan Hasil Belajar Pola Gambar dan Pola Bilangan menggunakan Model Problem Based Learning di Kelas IV SDN 24 Ujung Gurun - Octari, Dwi Ranti; Masniladevi, Masniladevi (TSAQOFAH, 2025)
Low student achievement, due to limited engagement in learning activities and a lack of experience in discussion and group collaboration, reflects the continued dominance of teacher-centered instruction. This study aims to describe the improvement of student learning outcomes on the topics of pattern recognition and number patterns through the implementation of the Problem Based Learning (PBL) model in Grade IV at SDN 24 Ujung Gurun. The research employed Classroom Action Research (CAR) using both quantitative and qualitative approaches, conducted over two cycles, each comprising planning, implementation, observation, and reflection stages. Data collection techniques included observation, tests, and non-test instruments. The research subjects were the classroom teacher (as observer), the researcher (as practitioner), and the fourth-grade students. The results revealed significant improvements across various aspects: the quality of instructional modules increased from 87.49% to 95.83%; teaching performance from 85.71% to 94.63%; student participation from 82.14% to 92.85%; and learning outcomes from a score of 75.54 to 87.65. These findings confirm that the implementation of the Problem Based Learning model is effective in improving student learning outcomes while also promoting active engagement in the learning process.